Alcohol detoxification in Ysbyty Gwynedd: Two small sips or one big gulp? Two-step screening more reliable for identification of alcohol dependency syndrome at risk of delirium tremens for routine care. Issue 1 (16th July 2015) - Salman, Muhammad; Subbe, Christian
Abstract: Compliance with pathways for hospitalised patients with alcohol dependency syndrome is often poor. A pathway for recognition and treatment of alcohol dependency was redesigned as part of a 12 month service improvement project in the acute medical unit using plan, do, study, act (PDSA) cycles. A needs assessment was undertaken: Audit data from 2013 showed over-prescription of chlordiazepoxide for detoxification treatment (DT) leading to prolonged hospital admissions with an average length of stay of 5.5 days in 2012/2013. Acceptability of screening tools was tested: Common screening tools (CEWA, AUDIT) were rejected by junior doctors due to the high number of questions as too cumbersome for routine practice. Compliance with usage in random samples over a three month period was persistently <10%. Testing of an abbreviated AUDIT questionnaire with only two questions and a specified threshold showed a AUROC of 1 (p<0.001 for correct identification). The screening tool was implemented in several PDSAs cycles. After the final cycle a random sample of 100 patients was reviewed for pathway compliance over a three months period. Eighty-six patients were screened with the two-question tool of these 18 were identified as possible risk. Of these 16 patients had the full AUDIT questionnaire, only eight with elevated values were started on DT. Overall compliance with the pathway increased to 84%.